Enabling and constraining factors for organic agriculture in Europe: a spatial analysis - Evelina Sandström; Esther Boere; Tamás Krisztin; Peter H Verburg (Environmental Research: Food Systems)
The European Commission has set a target of making 25% of its agricultural land organic by 2030. This is part of the farm-to-fork strategy to produce high-quality food in a more environmentally friendly way. However, there are large disparities between and within member states in the share of agricultural land currently managed as organic. Current statistics available on organic agriculture in the EU are limited to national or subnational scale. In addition to that, studies on location factors of organic agriculture are mostly conducted at the national or subnational level. This constitutes a major obstacle in formulating policies to improve the share of organic agriculture within Europe. This study analyses the influence of socioeconomic, climate, and biophysical variables on the spatial distribution of certified organic producers at high resolution throughout Europe. To do so, it maps the location of current organic agriculture throughout Europe, using detailed postcode-level data from certification registries. Subsequently, regression analysis at NUTS 2 and 1 km ^2 resolution identify the driving forces for their location. The results indicate that organic agriculture is found predominantly in areas close to markets and with unfavourable biophysical conditions for conventional agriculture. Population density was found to be the single strongest indicator increasing the odds of organic agriculture by 271%. We highlight areas in the EU lacking in uptake of organic agriculture and provide an understanding of what factors help create an enabling or constraining environment for adoption. Our results directly contribute to policy discussions on how to better target efforts for conversion to organic agriculture.